Mucilage Formation and Ecology - Ece Polat; Hülya Ünver; Mahmut Altınbaş (Doğal Afetler ve Çevre Dergisi)
Mucilage formation is a very complex phenomenon involving various biological and hydrological interactions. Mucilage is formed as a result of bacterial and phytoplankton-based activities in the environment. Oceanic shifts can provide an environment favorable for mucilage development; however, other factors also play a role in forming mucilage. Mucilage's microbiological structure and morphology, which have been studied in many waters and habitats since the 17th century, are also distinct. This is due to the fact that mucilage development is largely taxon-specific, and mucilage thickness and texture vary depending on environmental conditions. In mucilage studies, phytoplankton is the main component. A high level of organic matter and nutrients in the environment stimulates the formation of phytoplankton and the microenvironment. Furthermore, various water properties, such as temperature, fluidity, and so on, have an increasing effect on mucilage production. The purpose of this review is to describe how aggregates and mucilage are produced by dissolved organic matter (DOM) and microbial populations. Then, living groups discovered in the structure of mucilage during microbial ecology researches are discussed. Several examples of living organisms negatively affected by the development of mucilage were discussed following a detailed description of the dominant species observed in mucilage regions and case information.